Molecular Detection and characterization of viruses infecting greenhouse-grown tomatoes in Albania - Magdalena CARA; Amani BEN SLIMEN; Enea MITRI; Orges CARA; Dajana FRASHERI; Jordan MERKURI; Giuseppe PARRELLA; Toufic ELBEAINO (Phytopathologia Mediterranea)
During the 2023–2024 growing season, a total of 45 tomato greenhouses were visited across five major production regions of Albania (Berat, Lushnje, Fier, Tirana, and Shkodra). A total of 196 greenhouse-grown tomato leaf samples, representing 31 varieties, were collected from plants showing virus-like symptoms. All samples were tested by RT-PCR and qPCR assays for the possible presence of significant tomato-infecting viruses and viroids, including alfalfa mosaic virus (AMV), cucumber mosaic virus (CMV), tomato brown rugose fruit virus (ToBRFV), tomato yellow leaf curl virus (TYLCV), tomato chlorosis virus (ToCV), tomato infectious chlorosis virus (TICV), tomato mottle mosaic virus (ToMMV), tomato spotted wilt virus (TSWV), tomato mild mottle virus (ToMMoV), tobacco mosaic virus (TMV), pepino mosaic virus (PepMV), potato viruses X and Y (PVX, PVY), potato leafroll virus (PLRV), tomato apical stunt viroid (TASVd), and potato spindle tuber viroid (PSTVd). In addition, Next-generation sequencing (NGS) using Illumina and MinION nanopore technologies were performed to characterize the complete genome of two Albanian ToBRFV isolates. RT-PCR and qPCR showed that ToCV, ToBRFV, AMV, and CMV were present in 25, 9.1, 4.1, and 4.1% of the samples, respectively, whereas all remaining viruses and viroids were absent. Illumina and MinION sequencing unveiled the complete genome sequences of ToBRFV (6,381 nucleotides) and of two additional viruses, i.e., Southern tomato virus, STV (3,437 nts) and tobacco vein clearing virus, TVCV (7,596 nts), both of which were not included in our initial screening. The two latter viruses were afterward diagnosed by PCR and found to be present in 2 and 3% of the tested samples, respectively. ToCV was most prevalent in Lushnje and Fier regions, while ToBRFV in Berat and Fier. The phylogenetic analyses predominantly clustered together the different Albanian viruses isolate, suggesting a local or regional origin. This study reports for the first time the presence of STV and TVCV in Albania and highlights the emergence of ToCV and ToBRFV in the country.